Imaging and Pathological Features of Alveolar Soft Part Sarcoma: Analysis of 16 Patients - Malvika Gulati (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Context Alveolar soft part sarcoma (ASPS) is a rare soft tissue tumor most commonly occurring in deep intramuscular plane of lower extremities of adolescents and young adults. It is a highly vascular, slow growing tumor with malignant potential having lung as the most common site of metastases at the time of presentation. Aims The aim is to review the imaging findings of ASPS and determine characteristic imaging features of this rare tumor. Materials and Methods Sixteen patients having histopathological diagnosis and preoperative imaging of ASPS attending the dedicated sarcoma clinic at our institute were included in the study. The demographic, clinical, and imaging data were retrieved from the case records and then evaluated for characteristic imaging features which may raise suspicion of ASPS. Results The patients ranged from 3 to 72 years of age and with a slight male preponderance. Of the eight CECTs evaluated, 62.5% tumors showed well-defined lobulated margins, 87.5% cases showed intense enhancement with presence of feeder vessels. On CEMRI of 10 patients, 70% had well circumscribed lobulated margins with intense enhancement and tortuous flow voids in most of them. All cases showed T2 hyperintense signal. Fourteen of 16 (87.5%) patients had metastatic disease with lung as the most common site (92.8%). Conclusion ASPS is a rare soft tissue sarcoma seen in children and young adults. Imaging may mimic a vascular malformation due to the presence of tortuous feeders. Misdiagnosis at an early stage may lead to later metastatic presentation of the disease, thus emphasizing the need to suspect it on imaging.